Hubungan antara Adiksi Internet, Tingkat Kecemasan, dan Kualitas Tidur dengan Kecerdasan Emosional - Evelyn Angie; Pela Meyadsa; Zaimah Hilal; Ahmad Ferdian Shobur; Subang Aini Nasution (SCIENTIA JOURNAL, 2023)
This study investigates the relationship between internet addiction, anxiety levels, and sleep quality with emotional intelligence among young adults in Jambi, Indonesia, in 2023. Utilizing a cross-sectional quantitative design, data were collected from 300 participants aged 18–25 years through validated questionnaires, including the Internet Addiction Test (IAT), the Hamilton Anxiety Rating Scale (HAM-A), the Pittsburgh Sleep Quality Index (PSQI), and the Emotional Intelligence Scale (EIS). The results revealed significant negative correlations between internet addiction and emotional intelligence (r = -0.43, p < 0.01), as well as between anxiety levels and emotional intelligence (r = -0.51, p < 0.01). Furthermore, poor sleep quality also exhibited a moderate negative relationship with emotional intelligence (r = -0.37, p < 0.01). These findings suggest that higher levels of internet addiction, increased anxiety, and lower sleep quality are associated with decreased emotional intelligence. The study highlights the importance of mental health and lifestyle management in the development of emotional regulation and psychological well-being in the digital era.